A 3D SVZonChip Model for In Vitro Mimicry of the Subventricular Zone Neural Stem Cell Niche - Ioannis Angelopoulos; Konstantinos Ioannidis; Konstantina Gr. Lyroni; Dimitris Vlassopoulos; Martina Samiotaki; Eleni Pavlidou; Xanthippi Chatzistavrou; Ioannis Papantoniou; Konstantinos Papageorgiou; Spyridon K. Kritas; Ioannis Grivas (Bioengineering)
Neural stem cells (NSCs) are crucial components of the nervous system, primarily located in the subventricular zone (SVZ) and subgranular zone (SGZ). The SVZ neural stem cell niche (NSCN) is a specialized microenvironment where growth factors and extracellular matrix (ECM) components collaborate to regulate NSC self-renewal and differentiation. Despite its importance, our understanding of the SVZ remains incomplete due to the inherent challenges of animal research, particularly given the tissue’s dynamic nature. To address these limitations, we developed a proof-of-concept, dynamic, and tissue-specific 3D organotypic SVZ model to reduce reliance on animal models. This static 3D organotypic model integrates a region-specific decellularized ECM derived from the SVZ, mimicking the native NSCN and supporting mouse-derived ependymal cells (ECs), radial glial cells (RGCs), astrocytes, and NSCs. To further improve physiological relevance, we incorporated a dynamic microfluidic culture system (SVZonChip), replicating cerebrospinal fluid (CSF) flow as observed in vivo. The resulting SVZonChip platform, combining region-specific ECM proteins with dynamic culture conditions, provides a sustainable and reproducible tool to minimize animal model use. It holds significant promise for studying SVZ-related diseases, such as congenital hydrocephalus, stroke, and post-stroke neurogenesis, while advancing translational research and enabling personalized medicine protocols.